Endophytic Bacteria From Bidara (Ziziphus mauritiana L.) Leaves and Its Activity Against the Pathogens Salmonella typhi and Escherichia coli - Mega Dwi Rhama; Dewi Chusniasih; Khaerunissa Anbar Istiadi; Erma Suryanti; Hida Arliani Nur Anisa (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2026)
Background: One possible source of bioactive substances is endophytic bacteria. These bacteria reside in plant tissues without harming the host plant. By generating unique chemicals in plant tissues and boosting the body's defense mechanisms against host plants, endophytic bacteria can manage infections. The purpose of this study is to investigate and describe the ability of endophytic bacteria from bidara leaves to create antimicrobial substances via their metabolite activities. Methodology: Nutrient Agar (NA) media was used exclusively for the isolation and culture of endophytic bacteria. Endophytic bacterial colonies were morphologically characterized both macroscopically and microscopically. Salmonella typhi and Escherichia coli growth inhibition was evaluated for endophytic bacterial metabolites (supernatants) with disc diffusion method. Chloramphenicol 0.3% used as positive control, and steriled aquadest as negative control. Findings: END01, END02, and END03 are the three endophytic bacterial isolates that were recovered. The three isolates differed in their edges and forms; END01 was Gram negative, whereas END02 and END03 were Gram positive. Isolate END01 and END03 selected for strong inhibition in antagonist tests against S. typhi (16.44 mm and 12.57 mm, respectively) compared to chloramphenicol control (45.86 mm). Their secondary metabolites were harvested at stationary phase, and chemical screening confirmed positive flavonoids in cell-free supernatants. The END01 supernatant showed the highest antimicrobial activity, with inhibition zones of 26.30 mm against S. typhi and 11.34 mm against E. coli, categorized as very strong and strong inhibition, respectively. Contribution: Endophytic bacteria isolated from the bidara leaves have the potential to inhibit the growth of pathogenic Salmonella typhi and Escherichia coli. This study represents the first reported exploration of endophytic bacteria from bidara leaves as flavonoid-producing antimicrobial agents against these clinically significant pathogens